PENERAPAN GIZI SEIMBANG DALAM UPAYA PENGELOLAAN DIABETES MELITUS DI KECAMATAN SUNGAI APIT - Tamal, Zahtamal; Putri, Fachriani; Restuastuti, Tuti; Chandra, Fifia; Restila, Ridha (2020, 2020)
Diabetes mellitus (DM) is a disease characterized by increased blood sugar levels (hyperglycemia). Based on data from the Sungai Apit Community Health Center, the number of people with DM (diabetesi) has increased from year to year. This condition is in line with the still not optimal efforts to control Diabetes in the community. The purpose of community service activities is the empowerment of cadres and diabetesi in preventing and managing diabetes, especially from the aspect of food management. Empowerment methods that have been carried out are counseling and training to improve the competence of Posbindu PTM cadres, as well as counseling to improve the understanding of diabetesi about managing food diets with question and answer lecture methods combined with simulations and the use of various educational media. This activity has been able to provide benefits to various parties, including the Department of Health, local government, Posbindu PTM cadres in terms of increasing understanding and competence to help prevent and control Diabetes through Posbindu PTM activities .